Exploring empathy of nursing students and the extent of their clinical experiences: a cross-case analysis - Cabataña, Pia Gabrielle E.; Dacayana, Yosef Liam A.; Jabagat, Jarrean B.; Palompon, Daisy R. (Jurnal Ners, 2024)
Introduction: Empathy is the ability of a nurse to understand the circumstances, experiences, and feelings of the patients. It is a vital component of a nurse as this enables the nurse to respond therapeutically to the needs of the clients, thereby providing quality nursing care. This study explored the development of empathy among nursing students based on their hospital exposure and other factors that provide a more in-depth understanding of the phenomenon investigated. Methods: Using the intrinsic case study method, the study interviewed six nursing students as informants, selected based on their extent of clinical exposure through purposive sampling. A standardized Jefferson Scale of Empathy (JSE) was also used to provide information on empathy. A cross-case analysis was used to generate the findings of this study. Results: Findings generated five themes: maintaining empathy level across different conditions, prior clinical experiences affect empathy levels, empathy increases with knowledge, expression of empathy is hindered by academic workload and mismatch between perceived and objectively measured empathy levels. Conclusions: Empathy was more developed by nursing students when they were exposed to patient care experiences. The extent of knowledge and the continued experience in the clinical field are major factors that contribute to their increased empathy levels of nursing students.